Interferon-induced IL-10 drives systemic T-cell dysfunction during chronic liver injury - Hackstein, Carl-Philipp; Spitzer, Jasper; Symeonidis, Konstantinos; Horvatic, Helena; Bedke, Tanja; Steglich, Babett; Klein, Sabine; Assmus, Lisa M.; Odainic, Alexandru; Szlapa, Jennifer; Kessler, Nina; Beyer, Marc; et al. (Journal of hepatology, 2023)
Background & Aims - Patients with chronic liver disease (CLD), including cirrhosis, are at increased risk of intractable viral infections and are hyporesponsive to vaccination. Hallmarks of CLD and cirrhosis include microbial translocation and elevated levels of type I interferon (IFN-I). We aimed to investigate the relevance of microbiota-induced IFN-I in the impaired adaptive immune responses observed in CLD. - Methods - We combined bile duct ligation (BDL) and carbon tetrachloride (CCl4) models of liver injury with vaccination or lymphocytic choriomeningitis virus infection in transgenic mice lacking IFN-I in myeloid cells (LysM-Cre IFNARflox/flox), IFNAR-induced IL-10 (MX1-Cre IL10flox/flox) or IL-10R in T cells (CD4-DN IL-10R). Key pathways were blocked in vivo with specific antibodies (anti-IFNAR and anti-IL10R). We assessed T-cell responses and antibody titers after HBV and SARS-CoV-2 vaccinations in patients with CLD and healthy individuals in a proof-of-concept clinical study. - Results - We demonstrate that BDL- and CCL4-induced prolonged liver injury leads to impaired T-cell responses to vaccination and viral infection in mice, subsequently leading to persistent infection. We observed a similarly defective T-cell response to vaccination in patients with cirrhosis. Innate sensing of translocated gut microbiota induced IFN-I signaling in hepatic myeloid cells that triggered excessive IL-10 production upon viral infection. IL-10R signaling in antigen-specific T cells rendered them dysfunctional. Antibiotic treatment and inhibition of IFNAR or IL-10Ra restored antiviral immunity without detectable immune pathology in mice. Notably, IL-10Ra blockade restored the functional phenotype of T cells from vaccinated patients with cirrhosis. - Conclusion - Innate sensing of translocated microbiota induces IFN-/IL-10 expression, which drives the loss of systemic T-cell immunity during prolonged liver injury. - Impact and implications - Chronic liver injury and cirrhosis are associated with enhanced susceptibility to viral infections and vaccine hyporesponsiveness. Using different preclinical animal models and patient samples, we identified that impaired T-cell immunity in BDL- and CCL4-induced prolonged liver injury is driven by sequential events involving microbial translocation, IFN signaling leading to myeloid cell-induced IL-10 expression, and IL-10 signaling in antigen-specific T cells. Given the absence of immune pathology after interference with IL-10R, our study highlights a potential novel target to reconstitute T-cell immunity in patients with CLD that can be explored in future clinical studies.
Online verfügbar: 2. März 2023, Artikelversion: 15. Juni 2023
Gesehen am 04.08.2023